Effects of dietary grape seed on performance and some metabolic assessments in Japanese quail with different plumage colors exposed to heat stress - Erisir, Zeki; Simsek, Ulku Gulcihan; Ozcelik, Mehtap; Baykalir, Yasin; Mutlu, Seda Iflazoglu; Ciftci, Mehmet (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2018)
The objective of this study was to determine the effects of grape seed (GS) supplementation to basal diet on performance, carcass characteristics, some biochemical parameters, and antioxidant status of tissues of Japanese quail in growth phase with different plumage colors exposed to heat stress (HS). A total of 144 eight-day-old Japanese quail including 72 (36 females, 36 males) grey and 72 (36 females, 36 males) golden were used in this study. The quail were kept under HS (16 h at 34 degrees C, 8h at 22 degrees C) and thermo-neutral (24 h at 22 degrees C) conditions between 15 and 43 days of age. All quail were fed a basal diet (control) and basal diet supplemented with GS at both 10 g/kg and 20 g/kg ratios. Each feeding treatment was repeated three times including four quail (two females and two males) per replicate. Heat stress considerably decreased the live weight gain on days 29-36, 36-43, and 15-43. Golden quail had higher live weight from the beginning of the trial. The increase of live weight on days 15-43 was higher in the golden group than in the grey group. Malondialdehyde (MDA) levels of liver and kidney tissues increased in heat-stress group compared with thermo-neutral group (P<0.001). In HS, significant increases were determined only in catalase (CAT) in the liver and in glutathione peroxidase (GSH-Px), CAT, and glutathione (GSH) in the kidney (P<0.05). Addition of dietary GS decreased MDA and antioxidant levels, which increased in liver and kidney of quail during HS. Plasma total cholesterol, alanine aminotransferase (ALT), and aspartate aminotransferase (AST) levels were higher in quail under HS. Plasma total cholesterol, glucose, triglyceride, AST, and ALT levels of quail under HS decreased due to addition of 10 g/kg GS.
Keywords: antioxidant; feed additive; heat stress; Japanese quail